PQRST Technique Toward Reading Comprehension of the Second Grade Students at SMAN 1 Kota Jambi - Dewi Syafitri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This research is aimed to investigate whether or not there is any significant effect of PQRST technique toward reading comprehension of second graders at SMAN 1 Kota Jambi.Preview, question, read, summary and test labeled PQRST is one of language teaching technique in reading comprehension. This technique can be used to solve students difficulties in comprehend the text and also can help the students to deepen their understanding of the text. The subjects were students of grade XI of SMAN 1 Kota Jambi. XI IA 1 was assigned as the experimental group and XI IA 2 was assigned as control group. The cluster sampling technique was used in this research. The design of this research is an experimental research to find out the cause and effect relationship between two variables. There are two data used in this research. The first data is pre test and the second is post test. After the data were collected, the researcher used t test analysis to see the significant difference between two variables. The result of this research showed that t test value was 3.15, at the level of significance 0.05 with df 60, the value of t table was 2.00. it is known that t test value was bigger than t table indicated the research hypothesis H1 was accepted where there is significance difference in students, reading comprehension between those who were taught by using PQRST technique and those who were taught without using PQRST technique. In summary, PQRST technique can help the students to comprehend the reading text well. Keywords: reading comprehension, PQRST technique